Hardware Support for Enforcing Isolation in Lock-based Parallel Programs - Ratanaworabhan, Paruj; Burtscher, Martin; Kirovski, Darko; Zorn, Ben (Proceedings of the 26th ACM International Conference on Supercomputing (ICS'12), 2012)
When lock-based parallel programs execute on conventional multicore hardware, faulty software can cause hard-to-debug race conditions in critical sections that violate the contract between locks and their protected shared variables. This paper proposes new hardware support for enforcing isolation of critical section execution. It can detect and tolerate races, allowing programs to execute race-free. Our hardware scheme targets the existing large code base of lockedbased parallel programs written in type unsafe languages such as C and C++. Our approach works directly on unmodified executables. An evaluation of 13 programs from the SPLASH2 and PARSEC suites shows that the cost of the additional hardware and the impact on the overall execution time is minimal for these applications. Our mechanism is complementary to hardware transactional memory in that it uses similar structures but focuses on enhancing the reliability of existing lock-based programs.